3568 Education. (27th March 2019) - Devi, Gayathri; McMains, Jennifer; Crabtree, Donna; Freel, Stephanie; Sudan, Rajan
Abstract : OBJECTIVES/SPECIFIC AIMS: The Duke Multidisciplinary Education and Research in Translational Science (MERITS) program was introduced with the goal of providing education and resources to faculty and trainees who are involved in translational research. However, the definition of what translational science is and entails can be widely variable, even within a single institution or department, which creates difficulties in appropriate dissemination of information regarding translational resources and assistance. This objective of this study was thus to obtain baseline information and views of translational science from a pilot population of Duke faculty. Based on data collected in a previous focus group, we expected to observe a lack of consensus regarding the definition and inclusion principles of translational science. METHODS/STUDY POPULATION: A digital survey was distributed to Duke Department of Surgery faculty regarding translational science, including opinions on definition, impacts, experienced barriers, known resources, and future training preferences. RESULTS/ANTICIPATED RESULTS: Ninety-five total responses were obtained, with 79.3% of respondents identifying their work as translational. There was no consensus on the precise definition of translational science, although the majority of respondents reported similar essential elements including multidisciplinary science and transitioning between investigative stages. Respondents noted that translational science increased their job satisfaction and recognition in their field, but also stated that they had experienced barriers to translational science. These barriers were primarily funding (56.4%) or lack of training (38.2%) related. DISCUSSION/SIGNIFICANCE OF IMPACT: The results of our pilot survey suggest that the MERITS program should focus on training investigators on the resources available for translational investigations and expound upon how it fits into and enhances their current and future research endeavors.